Biological control of plant diseases (Food Products Press, an imprint of the Haworth Press, 2007)
Biological Control of Plant Diseases presents up-to-date research findings on disease management to provide you with a single-source reference text for developing a sustainable ecosystem that doesn’t depend on harmful and unhealthy agrochemicals. This unique book acts as a catalyst for change, presenting fresh ideas and innovative strategies for finding meaningful solutions to the problems of disease control. Contributors working in the areas of plant protection, microbiology, plant pathology, biotechnology, ecology, and food safety examine topics that include the application of plant tissue culture, competitive root colonization, mycorrhiza in biocontrol, microbial siderophores, antagonism, and genetic regulation.